Genetics & human health : a journey within - Brynie, Faith Hickman (Brookfield, Conn. : Millbrook Press, 1995)
In examining the role that genetics plays in human health, this book introduces the essentials of genetics and looks at the ways in which scientists are attempting to correct genetic disorders.
Blueprint for life -- Father Gregor and his garden -- Enemies within -- Tinkering and tinkertoys -- The gene stalkers -- The gene doctors -- Memories of your journey.
Includes bibliographical references and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Human genetics -- Juvenile literature; Medical genetics -- Juvenile literature; Human genetics; Medical genetics; Genetics; Medical genetics